The effect of phase I treatment on serum cholesterol and triglyceride level in patients with periodontitis and hyperlipidemia - M Ketabi; F Rashidi Meibodi; Sh Amini; N Farkhani (Isfahan University of Medical Sciences, 2009)
Introduction: The association of periodontal infections and systemic diseases like coronary heartdisease, myocardial infarction, preterm labor, low weight delivery, diabetes, and hyperlipidemia hasbeen shown. In limited researches, the effect of periodontal treatments on reduction of serum glucoseand lipid levels has been studied. The aim of this research was evaluating the effect of phase Itreatment on the level of serum cholesterol and triglyceride in patients with periodontitis andhyperlipidemia.Materials & Methods: In this semi-experimental and interventional study, in 30 patients withperiodontitis and known hyperlipidemia, cholesterol and triglyceride were measured. Patients withgrade 3 and 4 of CPITN index were considered as periodontitis patients. Then periodontal treatmentincluding scaling, polishing, root planning and oral hygiene instructions were performed. One monthafter treatment, cholesterol and triglyceride were measured again. For statistical analysis, paired ttestwith SPSS was used.Results: Phase I treatment caused significant reduction of mean cholesterol (14.66 mg/dl; p value